2003
DOI: 10.1002/chem.200304711
|View full text |Cite
|
Sign up to set email alerts
|

Laser Spectroscopic Studies of Interactions of UVI with Bacterial Phosphate Species

Abstract: We have investigated the interactions of UVI with two bacterial phosphate-containing species: Gram-positive Bacillus sphaericus and Gram-negative Pseudomonas aeruginosa. The Gram-positive B. sphaericus was investigated by using Raman spectroscopy and time-resolved laser-induced fluorescence spectroscopy (TRLFS). We found that living cells, spores, and intact heat-killed cells complexed UVI (pH 4.5) through phosphate groups bound to their surfaces, while decomposed cells released H2PO4- and precipitated UVI as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…TABLE 5. EXAFS fit results for C, P, and U-O-P multiple-scattering shells and U-O dist SS shells from fits to residual spectra (model B) spectroscopy (37), Raman spectroscopy (27), and time-resolved laser-induced fluorescence spectroscopy (27,37,44). In addition, synchrotron-based techniques such as X-ray absorption spectroscopy have been used to determine the oxidation state (XANES) and to identify the number of atoms and their distances in the local structural environment (EXAFS) of U within a variety of microbial samples (22,26,(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…TABLE 5. EXAFS fit results for C, P, and U-O-P multiple-scattering shells and U-O dist SS shells from fits to residual spectra (model B) spectroscopy (37), Raman spectroscopy (27), and time-resolved laser-induced fluorescence spectroscopy (27,37,44). In addition, synchrotron-based techniques such as X-ray absorption spectroscopy have been used to determine the oxidation state (XANES) and to identify the number of atoms and their distances in the local structural environment (EXAFS) of U within a variety of microbial samples (22,26,(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Cultures of Citrobacter sp. (Yong and Macaskie, 1998), Acidithiobacillus ferrooxidans (Merroun et al, 2002), Bacillus sphaericus (Knopp et al, 2003), and Acinetobacter johnsonii (Boswell et al, 1999) have been demonstrated to remove uranium from water using a phosphate release mechanism. Under aerobic growth conditions, these microorganisms can accumulate phosphorus intracellularly in the form of polyphosphate (polyP) granules (Groenestijn et al, 1988;Tandoi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…(Macaskie et al, 1992;Young and Macaskie, 1995;Jeong et al, 1997) and of Bacillus sphaericus (Knopp, et al, 2003); others observed the accumulation of U(VI) as needlelike fibrils on the cell surface of S. cerevisiae (Strandberg, et al, 1981;Volesky and May-Philips, 1995). However, the mechanisms whereby microorganisms cause the precipitation of uranium are poorly understood, and the U-bearing precipitates have not been properly characterized.…”
Section: Introductionmentioning
confidence: 99%